Transauricular intra-arterial and intravenous digital subtraction angiography for abdominal aortic aneurysm imaging in a rabbit model. (June 2017) - Bi, Yonghua; Yu, Zepeng; Xu, Ke; Zhong, Hongshan; Wu, Gang; Han, Xinwei
Abstract: Aim: The aim of this study was to evaluate transauricular digital subtraction angiography (DSA) as an alternative to conventional intra-arterial DSA for rabbit abdominal aortic aneurysm (AAA). Materials and methods: AAA models were created in 8 New Zealand white rabbits by sewing vein patch. The diameters of aortic arteries were measured by DSA via ear vein and ear central artery. The common carotid artery (CCA) was exposed and cannulated for DSA as conventional angiography. Diameter size was measured and compared. Results: Aortic diameters, tested by DSA via ear vein, ear central artery and CCA were 7.9 ± 1.2 mm, 7.8 ± 1.0 mm and 7.9 ± 1.1 mm respectively, with no significant differences. Angiography via CCA as standard procedure, correlation in aneurysm neck diameter was r = 0.93 for IVDSA and r = 0.96 for angiography via central artery ( P  < 0.01); Correlation in AAA diameter was r = 0.99 for IVDSA and r = 0.99 for angiography via central artery ( P  < 0.0001). Conclusions: Transauricular DSA shows good correlation to conventional DSA, can be used repeatedly with less invasiveness, and suitable for rabbit AAA follow-up study. Highlights: Correlations of DSA via ear vein and ear central artery to conventional DSA were good. Transauricular DSA shows good correlation to conventional DSA. Transauricular DSA can be used repeatedly with less invasiveness, and suitable for rabbit AAA follow-up study.